The first step in determining the solution to the system of equations, y = –x2 – 4x – 3 and y = 2x + 5, algebraically is to set the two equa

Question

The first step in determining the solution to the system of equations, y = –x2 – 4x – 3 and y = 2x + 5, algebraically is to set the two equations equal as –x2 – 4x – 3 = 2x + 5. What is the next step?

in progress 0
Ivy 13 mins 2021-10-14T13:20:05+00:00 2 Answers 0

Answers ( )

    0
    2021-10-14T13:21:12+00:00

    The next step will be solve for x.

    -x2-4x-3=2x+5

    -8x=8

    x=8/(-8)

    x=-1

    0
    2021-10-14T13:21:27+00:00

    Answer:

    not c

    Step-by-step explanation:

Leave an answer

45:7+7-4:2-5:5*4+35:2 =? ( )